Comparative Phytochemical Profile and Antioxidant Activity of Cocoa Beans Methanol Extract and its N-Butanol Fraction Obtained from Jembrana, Bali, Indonesia - Agung Ari Chandra Wibawa; Agung Nova Mahendra; Ida Bagus Putra Manuaba; I Nyoman Mantik Astawa (Riviera Publishing, 2024)
This study aims to evaluate the differences in phytochemical profiles and antioxidant activity between the methanol extract of cocoa beans and the n-butanol fraction obtained from Jembrana, Bali. Maceration technique was used in this research. The crude extract of cocoa beans was partitioned based on polarity to determine which fraction has the most potential as a source of bioactive compounds. The n-butanol fraction was evaporated to obtain a polar fraction from the methanol extract of cocoa beans. UV-Vis spectrophotometry was used to measure the total content of flavonoids and tannins in the methanol extract of cocoa beans and the n-butanol fraction. Research found that the methanol extract of Balinese cocoa beans had a total flavonoid content of 0.34 g/100 g and tannins of 0.37 g/100 g. However, the n-butanol fraction had a total flavonoid content of 15.34 g/100 g and tannin 20.16 g/100 g. The IC50 value of the methanol extract was 29.66 ?g/ml, while the n-butanol fraction was 2.63 ?g/ml. The AAI of the methanol extract was 1.35 and the n-butanol fraction was 2.63, indicating that the n-butanol fraction had stronger antioxidant activity with higher flavonoid and tannin content than the methanol extract. The implication of this research is that the n-butanol fraction of cocoa bean methanol extract has the potential as a source of bioactive compounds that can be utilized in the development of high added value products, especially in the context of food pharmaceuticals or other health product.